Validity and Reliability of Malay Version Physical Activity (BPA) Questionnaire among Nurses. - Sukhvinder, Singh Sandhu; Noor Hassim, Ismail; Krishna, Gopal Rampal (Universiti Kebangsaan Malaysia, 2015)
Introduction: Physical activity reduces risk of non-communicable diseases. Physical activity prevalence is low due to barriers to physical activity. This study was conducted to translate the Barrier to Physical Activity (BPA) questionnaire into Malay and assess the reliability and validity of the translated version among nurses. Methods: The Malay version of BPA was developed after translating the English version of BPA through back to back translation process. The Malay BPA was distributed among 306 volunteered nurses from 5 government hospitals in Selangor state. Factor analysis, Cronbach’s alpha test and test – retest reliability was conducted to determine psychometric properties of BPA. Results: Chronbach’s alpha coefficient was 0.79 for perceived benefits items and 0.51 for perceived barrier items (overall was 0.73). The ICC was 0.88 (95% CI: 0.78-0.93) for test-retest testing after 7 days. Two factors components were yielded through exploratory factor analysis with eigenvalues of 3.9 and 2.0 respectively. Both the factors accounts for 31.4 % of the variance. Factor 1 included 14 items and explained 19.9% of the variance. Factor 2 consisted of 5 items and explained 11.5% of variance. CFA yielded two factor structures with acceptable goodness of fit indices [x2/df = 23.99; GFI = 0.82, SRMR = 0.09; PNFI = 0.49 and RMSEA = 0.10 (90%CI = 0.09-0.11)]. Conclusions: The Malay version of BPA had demonstrated satisfactory level of validity and reliability to assess barriers to physical activity. Therefore, this questionnaire is valid in assessing barriers to physical activity among working population.